PENGARUH LEVERAGE DAN LIKUIDITAS TERHADAP PERINGKAT OBLIGASI - Hidayat, Wastam Wahyu (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The research aims to analyze the effect of, leverage, and Liquiditas on rating bond. Data were collected from 9 companies from non financial (bond) listed in Indonesia Stock Exchange (IDX) in 2012 to 2014. The analysis method of this research used multiple regression. The results showed that leverage had a negative and significant effect on rating bond and liquidity had a positive and significant effect on rating bon (p-value <0.05), Overall, the model's ability to explain rating bon is 23.00% Discussions and limitations are discussed in the paper. Keywords: promotion,above the line, below the line, management marketing